A mãe enlutada toma a palavra: Hilda Peña, de Isidora Stevenson, e Rosa Cuchillo, do Grupo Cultural Yuyachkani - Laura Gomes dos Santos (2022)
In this study, I analyzed the monologues Hilda Peña by Isadora Stevenson and Rosa Cuchillo by Grupo Cultural Yuyachkani. The main question was oriented by the possibility of these works to permit a reading of history against the grain aligned with the duties of the historical materialist according to Walter Benjamin (2012). The hypothesis was that the true events on which the monologues are base —the Bank O’Higgins robbery and the Internal Conflict in Peru—were disfigured and reconfigured in the dramaturgies through the narration of two women-mothers. Maybe they, who had lost their sons to State violence, could offer a new reading of history from a different perspective. The theoretical route of the study started with the examination of the theatrical form of the monologue, mainly with Pavis (2015) and Sinisterra (2009). To support the analysis of the works, I have approximated the concepts of monologue and trauma literature, following Seligman-Silva (2017); intimate theatre, according to Sarrazac (2013); and the reflections regarding narrative raised by Benjamin (2012). Moreover, considering the identity of the main characters and the theme addressed in the works, a review on gender, motherhood, and grief was carried out. In the analysis of the works, I came to the conclusion that the unrepresentability of trauma manifests itself in Hilda Peña and Rosa Cuchillo through the disfiguration provoked by the oneiric and mythical languages of the texts. In addition, I concluded that, strictly, the works do not function as rereadings of history. Yet, they do allow the audience, affected by the fictional account that was shared, to do it.